Respuesta :
Given trinomial
[tex]f(x)=x^2+bx-c[/tex]
If factors are (x+m)(x-n), then the expanded form of this expression must be identical to f(x), i.e.
[tex](x+m)(x-n)=x^2+(m-n)x-mn[/tex]
This means that it is necessary that
m-n=b
mn=c
if (x+m) and (x-n) are factors of f(x).
[tex]f(x)=x^2+bx-c[/tex]
If factors are (x+m)(x-n), then the expanded form of this expression must be identical to f(x), i.e.
[tex](x+m)(x-n)=x^2+(m-n)x-mn[/tex]
This means that it is necessary that
m-n=b
mn=c
if (x+m) and (x-n) are factors of f(x).
Answer:
Sample response: The value of m must be greater than the value of n. When you multiply the binomials, the middle term is the result of combining the outside and inside products. So, bx = –nx + mx, or bx = (–n + m)x. This means that b = –n + m. When adding numbers with opposite signs, you subtract their absolute values, and keep the sign of the number having the larger absolute value. Since b is positive, m must have the larger absolute value.